2016
DOI: 10.1212/wnl.0000000000003033
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of ABCD2 and ABCD3-I scores in TIA and minor stroke in the stroke unit setting

Abstract: Standard ABCD2 and ABCD3-I scores are useful instruments to estimate the probability of early and 3-month stroke in TIA and minor stroke patients treated at specialized stroke units, with C, D, and I being the most important score components in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Based on the above evidence, the researchers make supplement and revision to ABCD2 score, and founded ABCD2I grading system in 2010 which on the basis of ABCD2 score is added the presence of acute or chronic ischemic lesions on DWI ischemic lesions or on CT scan grading project (3 points), total score of 10 points. 5,[17][18][19] Researchers have confirmed that DWI, ABCD2 score has predictive value to TIA within 7 d after stroke risk, DWI positive, ABCD2 score results and can artery atherosclerosis be within 90 d after TIA independent risk factor for stroke, abnormal DWI results and patients with TIA etiology, warning its future increased risk for cerebral infarction. Scholars can estimate of risk for stroke after TIA based on ABCD2 score and whether there are infarcts in and CT and DWI, the result shows: the TIA within 7 d and 30 d after cerebral infarction predicted rate increased by 18%.…”
Section: Abcd2i Scorementioning
confidence: 95%
See 2 more Smart Citations
“…Based on the above evidence, the researchers make supplement and revision to ABCD2 score, and founded ABCD2I grading system in 2010 which on the basis of ABCD2 score is added the presence of acute or chronic ischemic lesions on DWI ischemic lesions or on CT scan grading project (3 points), total score of 10 points. 5,[17][18][19] Researchers have confirmed that DWI, ABCD2 score has predictive value to TIA within 7 d after stroke risk, DWI positive, ABCD2 score results and can artery atherosclerosis be within 90 d after TIA independent risk factor for stroke, abnormal DWI results and patients with TIA etiology, warning its future increased risk for cerebral infarction. Scholars can estimate of risk for stroke after TIA based on ABCD2 score and whether there are infarcts in and CT and DWI, the result shows: the TIA within 7 d and 30 d after cerebral infarction predicted rate increased by 18%.…”
Section: Abcd2i Scorementioning
confidence: 95%
“…5 The ABCD score is simple, fast and is suitable for screening the beginning of outpatient emergency patients, and includes age, blood pressure, clinical characteristics, and symptoms duration; ABCD score also focuses on the importance of unilateral limb weakness and duration of symptoms, obtaining good application. 7 ABCD score is used to predict TIA risk within 7d after stroke, and it can also be used to conduct health education to the public while allowing clinicians to rapidly screen increased risk in patients, thus guiding further treatment.…”
Section: Abcd Scorementioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence has shown that diffusion‐weighted imaging (DWI) abnormality and carotid stenosis ≥50% portend an increased risk of stroke. A number of studies showed that ABCD3‐I score, combining imaging factors with ABCD2 score, had a relatively higher predictive value than ABCD2 score, which relied on summation of points associated with clinical factors .…”
Section: Introductionmentioning
confidence: 99%
“…*These authors contributed equally to the manuscript (joint first authors). than ABCD2 score, which relied on summation of points associated with clinical factors [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%